PENGARUH FAKTOR SOSIAL DAN EKONOMI TERHADAP PENDAPATAN PEMBUDIDAYA IKAN MAS DI KECAMATAN DOLO SELATAN - Markisman, Markisman (Katalogis, 2016)
This study aims to: (1) To determine the household income and expenditure cultivators Goldfish in District South Dolo; (2) To determine the influence of social factors such as education, skills, experience, motivation to pursue business and system maintenance on the income of farmers in the district Goldfish South Dolo; and (3) To determine the influence of economic factors such as production costs, large pond, capital, production and the selling price to earnings Goldfish farmers in the district of South Dolo. This research is a descriptive analytic and execution of research using survey techniques. RTP 59 samples are selected by purposive sampling (intentional). Data were analyzed using Analysis of Income and Multiple Linear Regression Analysis (Multiple Regression). The results showed that: (1) The average income earned can sustain social and economic life of family farmers in the district Goldfish South Dolo Sigi; (2) Average household spending in Sub cultivators Goldfish South Dolo Sigi intended to meet the needs of non-compliance with food because food needs have been met with decent; and (3) the social and economic factors affect significantly (significantly) on the income of farmers in the district Goldfish South Dolo Sigi.